Citrus juice fermented with Lactobacillus plantarum YIT 0132 alleviates symptoms of perennial allergic rhinitis in a double-blind, placebo-controlled trial - Harima-Mizusawa, N; Kano, M; Nozaki, D; Nonaka, C; Miyazaki, K; Enomoto, T (Beneficial microbes, 2016)
This study aimed to examine whether citrus juice fermented with Lactobacillus plantarum YIT 0132 (LP0132), which was pasteurised after fermentation, could alleviate the symptoms of perennial allergic rhinitis in a double-blind, placebo-controlled, parallel-group trial. Subjects with perennial allergic rhinitis consumed LP0132-fermented juice (n=17) or unfermented citrus juice (placebo; n=16) once a day for 8 weeks. During the pre-intervention and intervention periods, the subjects recorded nasal symptoms (number of sneezing attacks, number of nose-blowing incidents, and stuffy nose score). The primary endpoint, nasal symptoms score (NSS), was scored from 0 to 4 according to the 'Practical Guideline for the Management of Allergic Rhinitis in Japan 2009' using a combination of the three nasal symptom items. Blood samples were collected at pre-intervention and at 8 weeks after commencing the intervention. There were several significant improvements not only in the LP0132 group but also in the placebo group because of potential anti-allergic effects of citrus. Compared with the placebo group, the LP0132 group showed a significant reduction in the NSS and stuffy nose score during the intervention period. Also, the LP0132 group, but not the placebo group, showed significant attenuation of type 2 helper T cells (Th2 cells)/helper T cells, serum total immunoglobulin E (IgE), and eosinophil cationic protein (ECP), and showed significant augmentation of type 1 helper T cells (Th1 cells)/Th2 cells at 8 weeks of intervention compared with baseline. It is suggested that daily intake of fermented citrus juice containing heat-killed LP0132 has beneficial effects on symptoms of perennial allergic rhinitis, and these benefits may be associated with the attenuation of Th2 cells, total IgE, and ECP via the immunomodulating activities of LP0132.